Wissenschaftliche Grundlagen zum Strategiediskurs für einen nachhaltigen Pflanzenbau: Scientific Basis for the Strategy Discourse on a Sustainable Crop Production - Feike, Til; Frei, Michael; Germeier, Christoph; Herrmann, Antje; Hülsbergen, Kurt-Jürgen; Kaul, Hans-Peter; Komainda, Martin; Kottmann, Lorenz; Möller, Kurt; Nendel, Claas; Pasda, Gregor; Pekrun, Carola; et al. (Bodenkultur, 2022)
Scientific facts about the relationships between the goals are indispensable for the rational social discourse on solving the various conflicting goals on the way to sustainable crop production. Therefore, the German Society for Agronomy has compiled scientific findings on the topics of biodiversity, climate relevance and climate resilience, nutrient management, crop protection, soil protection and production of renewable raw materials, and identified the existing need for research. After an executive summary that highlights the findings, the subject areas are explained in detail. The purpose of this paper is not to make recommendations for policy-making, but to support the public debate by providing factual information.